2021
DOI: 10.1007/s00704-021-03686-x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of regional rainfall data in homogeneous clustering of data-sparse areas: a study in the upper Brahmaputra valley region

Abstract: Delineation of homogeneous regions has found its way into many hydrological applications as it helps in addressing the challenges in understanding the behavior of rainfall distribution and its variability at a local scale. In the present study, rainfall data recoded by 83 tea gardens in the upper Brahmaputra valley region of Assam have been used to identify homogeneous rainfall regions by using fuzzy clustering analysis. Further, seven different cluster validity indices (CVs) were utilized to find out the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Methods such as Regional Frequency Analysis (RFA) have been frequently employed in such situations that transfer data from gauged locations to places with little or no data [1,2]. Several studies can be found with the application of the RFA technique in the region [3][4][5][6][7]. Regional frequency analysis of extreme rainfall for any region aims to provide a detailed description of the distribution of rainfall events and predict probable estimates for a given return time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods such as Regional Frequency Analysis (RFA) have been frequently employed in such situations that transfer data from gauged locations to places with little or no data [1,2]. Several studies can be found with the application of the RFA technique in the region [3][4][5][6][7]. Regional frequency analysis of extreme rainfall for any region aims to provide a detailed description of the distribution of rainfall events and predict probable estimates for a given return time.…”
Section: Introductionmentioning
confidence: 99%
“…Notable recent studies on the comparison of uncertainty analysis of rainfall from regional and at-site analysis can be found in the studies of [14][15][16], but very scarce studies are available for north east India. The available studies are limited to only selection of probability distribution and estimation of quantiles [3,5]. Resulting quantiles from RFA with small sample sizes are speculative, and constructing confidence intervals has been the simplest and most widely used approach to evaluate the uncertainty.…”
Section: Introductionmentioning
confidence: 99%